Studying the Structural Phase Composition and Optical and Mechanical Properties of Al–Si–Re–O Coatings Deposited on Quartz Glass; Russian Physics Journal; Vol. 67, iss. 4 - Tursunkhanova R. Ryskul; Sergeev V. P. Viktor Petrovich; Kalashnikov M. P. Mark Petrovich; Sergeev O. V.; Voronov A. V.; Stuzhuk V. V. (2024, 2024)
Title screen